VADNet: A Novel Deep Learning Architecture for Automatic Detection and Classification of Abnormalities from Public Surveillance Videos - Gs Naveen Kumar, Ganta Raju (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Usage of public surveillance cameras in cities and other places of public importance has resulted in reduction of crimes besides helping in establishing evidences of certain incidents. Thus, video analytics has become indispensable research area. With technological innovations like cloud computing, Internet of Things (IoT) and Artificial Intelligence (AI), storage and analysis of videos in real time is made possible. At the same time, emerging techniques in deep learning have paved way for processing of image content leading efficient video analytics. Abnormality detection from surveillance videos has assumed significance. The existing research in this area based on Convolutional Neural Network (CNN) has limitations because of the fact that it cannot bestow optimal performance unless, it is customized to solve the problem in hand. Towards this end, in this paper, we proposed a novel deep learning architecture known as Video Abnormality Detection Net (VADNet) for detection of abnormalities from surveillance videos. VADNet is a CNN variant designed for leveraging detection performance. We proposed an algorithm named Learning based Video Abnormality Detection (LbVAD) which exploits VADNet for efficient detection of video abnormalities. UCF-Crime is the benchmark dataset used for our empirical study. Our experimental results revealed that VADNet outperforms existing CNN variants like MobileNetV1, ResNet50 and VGG19 models with highest accuracy 95.64%.